2023
DOI: 10.1200/jco.22.02366
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Phase II Trial of Fecal Microbiota Transplantation Versus Placebo in Allogeneic Hematopoietic Cell Transplantation and AML

Abstract: PURPOSE Gut microbiota injury in allogeneic hematopoietic cell transplantation (HCT) recipients and patients with AML has been associated with adverse clinical outcomes. Previous studies in these patients have shown improvements in various microbiome indices after fecal microbiota transplantation (FMT). However, whether microbiome improvements translate into improved clinical outcomes remains unclear. We examined this question in a randomized, double-blind, placebo-controlled phase II trial. METHODS Two indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 72 publications
2
19
0
Order By: Relevance
“…Varying conditioning regimens induce varying levels of MBI, and thus microbial phenotypes and their associated clinical implications. Of interest, the recent trial conducted by Rahsidi et al investigating FMT for BSI prevention in HSCT recipients did not reach its primary endpoint, that is, FMT did not significantly reduce the incidence of BSI [36]. This may reflect the fact that although microbes were successfully delivered to recipients, their ability to durably colonize the gut may be impacted by persistent mucosal damage.…”
Section: Key Pointsmentioning
confidence: 99%
“…Varying conditioning regimens induce varying levels of MBI, and thus microbial phenotypes and their associated clinical implications. Of interest, the recent trial conducted by Rahsidi et al investigating FMT for BSI prevention in HSCT recipients did not reach its primary endpoint, that is, FMT did not significantly reduce the incidence of BSI [36]. This may reflect the fact that although microbes were successfully delivered to recipients, their ability to durably colonize the gut may be impacted by persistent mucosal damage.…”
Section: Key Pointsmentioning
confidence: 99%
“…While statistical differences were not observed in this clinical trial, it still acknowledges the positive value of FMT in the context of HSCT. 118 , 119 Van den Brink’s lab explored the value of the intestinal microbiota in recipient hematopoietic system reconstruction after bone marrow transplantation. They found that in mice lacking intestinal microbiota, there is impaired hematopoietic system reconstruction after bone marrow transplantation.…”
Section: Targeting Gut Microbiota To Regulate Hematopoiesismentioning
confidence: 99%
“…FMT was safe and ameliorated intestinal dysbiosis. 10 The large number of ARGs analyzed (47 ARGs), access to longitudinal stool samples collected over 9 months, and the randomized design of the trial allowed us to address the three knowledge gaps of interest.…”
Section: Introductionmentioning
confidence: 99%